Identification and florfenicol-treatment of pseudomonas putida infection in gilthead seabream (Sparus aurata) fed on tilapia-trash-feed - Ibrahim M. Aboyadak; Mohsen Abdel-Tawwab; Nadia G. Ali (BMC Veterinary Research, 2024)
Abstract The present study aimed to determine the major cause of the high mortality affecting farmed gilthead seabream (Sparus aurata) and controlling this disease condition. Fifteen diseased S. aurata were sampled from a private fish farm located at Eldeba Triangle, Damietta, fish showed external skin hemorrhages, and ulceration. Bacterial isolates retrieved from the diseased fish were identified biochemically as Pseudomonas putida and then confirmed by phylogenetic analysis of the 16 S rRNA gene sequence. P. putida was also isolated from three batches of tilapia-trash feed given to S. aurata. Biofilm and hemolytic assay indicated that all P. putida isolates produced biofilm, but 61.11% can haemolyse red blood cells. Based on the antibiotic susceptibility test results, P. putida was sensitive to florfenicol with minimum inhibitory concentrations ranging between 0.25 and 1.0 µg mL− 1, but all isolates were resistant to ampicillin and sulfamethoxazole-trimethoprim. Pathogenicity test revealed that P. putida isolate (recovered from the tilapia-trash feed) was virulent for S. aurata with LD50 equal to 4.67 × 107 colony forming unit (CFU) fish− 1. After intraperitoneal (IP) challenge, fish treated with 10 mg kg− 1 of florfenicol showed 16.7% mortality, while no mortality was recorded for the fish group that received 20 mg kg− 1. The non-treated fish group showed 46.7% mortality after bacterial challenge. HPLC analysis of serum florfenicol levels reached 1.07 and 2.52 µg mL− 1 at the 5th -day post-drug administration in the fish groups received 10 and 20 mg kg− 1, respectively. In conclusion, P. putida was responsible for the high mortality affecting cultured S. aurata, in-feed administration of florfenicol (20 mg kg− 1) effectively protected the challenged fish.